Etika Politik dalam Pengurusan Partai Demokrasi Indonesia Perjuangan (PDIP) Provinsi Sumatera Utara - Darajat, Muhammad Ikmal; Katimin, Katimin; Paralihan, Hotmatua (Medan Resource Center, 2025)
This study examines the implementation of political ethics in the management of the Indonesian Democratic Party of Struggle (PDIP) in North Sumatra. It focuses on decision-making, cadre formation, political campaigns, discipline enforcement, and the impact of political ethics on public perception and party performance. Using a qualitative descriptive approach, the study incorporates in-depth interviews with PDIP cadres, students, and community members, along with document analysis of internal policies. Findings reveal that PDIP North Sumatra has integrated political ethics through transparency, moral-based cadre training, and ethical campaigning. However, challenges remain, including external political pressure, a pragmatic local political culture, and internal resistance to change. Despite these obstacles, consistent adherence to political ethics has enhanced the party’s image, strengthened public trust, and improved its political standing. The study concludes that successful political ethics implementation depends on leadership, organizational culture, and external political dynamics. Recommendations include strengthening internal oversight, enhancing political education for cadres, and collaborating with independent institutions to ensure ethical governance. This research contributes to understanding how political ethics shape local party dynamics and democratic development in Indonesia.